ANALYSIS OF TRADITIONAL AND DIGITAL BANKING SYSTEMS ON CUSTOMER TRUST AND PURCHASING DECISIONS BY USING TECHNOLOGICAL INNOVATION ADOPTION AS MEDIATION - Steffani Beatrix Nur’ain Lule; Umi Narimawati; Bahtiar Usman (Adisam Publisher, 2026)
This study aims to analyze the influence of traditional and digital banking systems on customer trust and purchasing decisions with the adoption of technological innovation as a mediating variable. The population of this study is bank customers domiciled in the Greater Jakarta area who have made online transactions or use mobile banking and ATM services at least once. The sampling technique used is non-probability purposive sampling with a total of 200 respondents. Data analysis is quantitative using the Structural Equation Modeling (SEM) method with the assistance of the LISREL 8.80 program. The result shows that bank branch offices, mobile banking, and artificial intelligence (AI) have a positive and significant effect on customer trust. Meanwhile the presence of ATMs, transfer fees, interest rates, and social media marketing have no direct effect. The adoption of technological innovation has proven to mediate the positive influence of digital factors such as mobile banking, AI, and interest rates on customer trust. Customer trust has a significant effect on purchasing decisions. The originality of this study lies in positioning of technological innovation adoption as a mediating variable that bridges the relationship between banking system transformation and the building of customer trust. It emphasizes the role of technological innovation adoption as a determining factor in the success of banking digitalization in Indonesia